THE IMPACT OF SOCIAL MEDIA ON MENTAL HEALTH (Web of Teachers: Inderscience Research, 2026)
This research examines the multifaceted relationship between social media consumption and psychological well-being in the digital era. As social media platforms become deeply integrated into daily routines, their influence on mental health has emerged as a critical area of study. This article analyzes the correlation between prolonged platform engagement and various psychological outcomes, including anxiety, depression, sleep disturbances, and the "Fear of Missing Out" (FOMO). Furthermore, the study explores the role of social comparison mechanisms and the impact of cyberbullying on adolescent development. By synthesizing current findings, the research highlights both the detrimental risks and the potential for digital connectivity to provide social support, concluding with recommendations for balanced digital hygiene and policy-driven interventions to safeguard public mental health. The study further investigates the neurobiological triggers associated with dopamine-driven feedback loops and the physiological consequences of blue light exposure on sleep hygiene. It differentiates between active and passive engagement patterns, providing a holistic view of digital identity fragmentation.